Tratamento das cardiopatias congênitas em Sergipe : proposta de racionalização dos recursos para melhorar a assistência - Leite, Débora Cristina Fontes (2011)
Congenital heart defects are the most frequent congenital malformation being present in eight of every 1000 live births and showing the surgical produces in eighty percent of the cases. The aim of this study was to analyze the factors related to the deficit in the surgical correction of congenital heart disease in Sergipe in the last ten years. Data were collected from records of extracorporeal circulation common to all hospitals in Sergipe from January 1, 2000 to December 31, 2009, composed by the following variables: age, gender, origin, prognosis, postoperative diagnosis, type of surgery, hospital where the procedure was performed, type of medical care, surgical risk category RACHS -1. Data of births and deaths caused by heart disease in the years of study. The study was divided into two periods according to the centralization of resources in a single hospital from 2007. Performed 932 surgeries in ten years. There was reduction in surgery deficit from 69% in the pre-agreement to 55.3% in the post-agreement, 62.8% of the surgery happened between 1-12 years aged. Females had 55% of cases. The SUS system was the most common health care and the VSD was most frequent diagnosis (20.5%), followed by the Patent ductus arteriosus (20,2%) and the Interatrial Communication (19%). The predictors of hospital mortality were age, category RACHS -1 and Hospital where the procedure was performed. Our results indicate that the centralization of human and materials resources is important for the congenital heart surgery, is needed to expand these centers increase their productivity and, thereby, the quality of service. There was difference between the periods in the hospital mortality, pre-agreement 9,8% e post-agreement 5,4%.